Development of biodegradable antibacterial cellulose based hydrogel membranes for wound healing - Lacin, Nelisa Turkoglu (ELSEVIER, 2014)
Cellulose-based hydrogels have wide applications in tissue engineering and controlled delivery systems. In this study, chloramphenicol (CAP) loaded 2,3 dialdehyde cellulose (DABC) hydrogel membranes were prepared, characterized and their antibacterial efficacy was evaluated. Bacterial cellulose (BC) secreted by Acetobacter xylinum was modified to become DABC by oxidation via the sodium metaperiodate method. CAP-BC and CAP-DABC interactions were illustrated via ATR-FTIR analysis. Water retention capacity of BC and DABC membranes were determined as 65.6 +/- 1.6% and 5.3 +/- 0.3%, respectively. CAP release profiles were determined via HPLC analysis. The drug-loading capacities of BC and DABC membranes were 5 mg/cm(2) and 0.1 mg/cm(2), respectively. Membranes released 99-99.5% of the contained CAP within 24 h and an initial burst release effect was not observed. In vitro antibacterial tests of BC and DABC, both CAP-loaded, demonstrated their ability to inhibit bacterial growth for a prolonged duration. Antimicrobial effect against bacteria was still prevalent after 3 days of incubation period with disc diffusion tests. The MU test results reveal that fibroblast adhesion and proliferation on CAP-loaded DABC membranes were noticeably higher than CAP-loaded BC membrane. This newly developed drug containing DABC membranes seem to be highly suitable for wound healing due to its unique properties of biodegradability, biocompatibility, and antimicrobial effectiveness. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Wound healing; 2,3 Dialdehyde bacterial cellulose; Antibacterial activity; PERIODATE-OXIDATION; DRUG-DELIVERY; BACTERIAL; CHLORAMPHENICOL; BIOSYNTHESIS; SCAFFOLDS; RELEASE; THERMO; Biochemistry & Molecular Biology; Chemistry; Polymer Science